Instagram: as publicações de "amigos virtuais" como ativadores do consumo de usuários - Barbosa, Maria Naftally Dantas (Universidade Federal Rural do Semi-Árido, 2019)
The activation process is a recurrent process of the priming effect, constituted by influence and persuasion tactics that unleashed conscious or unconscious automatic answers, influencing stereotypes, actions and subsequent behavior. Thus, this investigation aims to analyze how virtual friends followed’ posts on the social networking Instagram can activates users’ consumption. In order to achieve this general objective, the following specific objectives were determined: (I) to identify whether consumption can be activated in Instagram; (II) to verify the profile of the network of contacts that activate the consumption; (III) to investigate the positive and negative attributes of the posts that perform this activation in users. A qualitative case study was carried out with active users in two steps: through group and individual interviews. A total of thirty-three subjects took part in the semi-structured interviews that were analyzed through content analysis with the support of the Atlas.ti software. The results confirm that the consumption can be activated and indicated that the users are conscient in what regards the stimuli to which they are exposed, and, in addition, they are able to realize the effects of this influence on their consumption. Family, friends, artists/digital influencers’ posts are the ones that the users consider the most when deciding to purchase something. These people have profiles that present expressiveness, proximity, trust, similar preferences and expertise. The positive and negative aspects of the posts were highlighted, making it possible to understand that the quality of the shared content has an important role on the activation process, since Instagram is a visual social networking. Based on the achieved results, it is possible to say that followed friends’ posts activate consumption through different ways, however, this only occurs if there are pre-existent mental representations, i.e., the desire and the purchase intention must have already been internalized in the users’ memory. The main contribution of this research, then, is to offer empirical-theoretical backing on consumption activation at its virtual context, so that researchers, companies and professionals may know the consumer, as well as the content produced by this individual and then use it strategically in their actions
Keywords: Ativação do consumo; Instagram; Amigos virtuais; Comportamento do consumidor; Consumption activation; Instagram; Virtual friends; Consumer’s behavior; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES